How non-conventional machining affects the surface integrity and magnetic properties of non-oriented electrical steel. (15th November 2021) - Winter, Kieran; Liao, Zhirong; Ramanathan, Ramkumar; Axinte, Dragos; Vakil, Gaurang; Gerada, Christopher
Graphical abstract: Highlights: Machining causes magnetic deterioration in non-oriented electrical steels. Induced sub-granular misorientations act as pinning sites for magnetic domains. Magnetic domains may become disordered near to the machined edge. Abrasive waterjet cutting was found to minimally deteriorate the magnetic properties. Abstract: Non-oriented electrical steel (NOES) laminations are commonly used to manufacture the rotor and stator core of electric machines. To achieve high machine efficiencies, it is desirable for these NOES laminations to be able to achieve a high saturation magnetisation whilst incurring minimal core losses. It is known that inappropriate machining of these laminations could cause significant deterioration in their magnetic properties. However, the mechanisms by which machining influences this deterioration are less understood. This study investigates the magnetic deterioration after four nonconventional machining methods: Abrasive Waterjet, Wire Electric Discharge Machining, Pulsed Laser, and Continuous Wave Laser. An in-depth investigation of surface integrity through a range of methods, i.e., surface topography, scanning electron microscopy (SEM), nanoindentation, electron backscatter diffraction (EBSD), and magnetic domain imaging, were conducted to study the mechanisms causing magnetic deterioration. The surface integrity after machining using conventional methods (e.g., microstructure and texture), was found to not be of high relevance unless this is combined with analysis on how machining affects the micro-magnetic domain structure. This paper, for the first time, highlights this aspect and attempts to make initial quantitative evaluations on how the magnetic domains are affected in the superficial layer that is the result of non-conventional machining.